Writers’ self-commentaries: the potential of meanings (Ivan Turgenev and Ivan Goncharov) - Володина, Наталья (Acta Universitatis Lodziensis. Folia Litteraria Rossica, 2018)
The article is devoted to two authors’ commentaries on their own works: Ivan Turgenev’s – on his novel Fathers and Sons and Ivan Goncharov’s concerning The Precipice. Both writers provided explanations in view of the fact that their works continued to arouse controversy long after they had been published. The crucial issue for critics as well as for the readership was the authors’ attitude to their nihilist characters, Evgeny Bazarov and Mark Volokhov respectively. When explaining his position, either author talks about the novel’s conception, reconstructs the process of creation, living through it again; at the same time, they already look at their creations from a distance. The clarifications offered by Turgenev and Goncharov “outside” the literary text proper are revealing in terms of which aspects of the interpretative potential were particularly important for them, how well these correlate with what is said in the literary work itself and what is “heard” by the readership.